THE CORE COMPONENT OF FORGIVENESS: ANASAKTI AS A SIGNIFICANT PREDICTOR OF FORGIVENESS IN INDIAN MARRIED COUPLES - Tuli, Garima; Tiwari, Priyanka (International Journal of Psychosocial Rehabilitation, 2020)
The popular notion for creating a successful marriage is love, passion, chemistry, kindness, goodness, faithfulness, friendship, and gentleness. However, the concept of dispassion has yet not been evaluated in this light which has been mentioned in the Indian texts such as Bhagavad Gita. As the divorce rates in India are increasing at a rapid rate, it becomes crucial to understand the unique unexplored qualitatives’ that are essential to resolve conflicts in marriage. Thus the Indian concept of Anasakti and Forgiveness were used as potential variables for exploration in this study on Indian marital couples. Enough research has happened on what creates a good marriage but what are the qualities that one needs to individually cultivate to resolve conflict. In this light forgiveness and Anasakti have been studied in relation to each other in the present investigation. The study was conducted using standardized tools on Anasakti (Asakti-Anasakti Scale) and Forgiveness (The Heartland Forgiveness Scale) on a sample of 100 marital couples. The sample was selected from Delhi NCR on working professionals who were in a consistent wedlock for 5 to 15 years. The couples were briefed about the study and the respective questionnaires on Anasakti & Forgiveness were administered. Mean, correlation and regression analysis were calculated to understand relationship between Anasakti & Forgiveness. Results: Anasakti significantly predicts Forgiveness (r=-.545, p<0.01) in Indian marital couples yet it does indicate any difference on the two variables in context of gender.